Validation and reliability of the Dutch version of the EORTC QLQ-NMIBC24 Questionnaire Module for patients with non-muscle-invasive bladder cancer - Theodora M. Ripping; Ellen Westhoff; Neil K. Aaronson; Mieke Van Hemelrijck; Elke Rammant; J. Alfred Witjes; Lambertus. A. Kiemeney; Katja K. H. Aben; Alina Vrieling (SpringerOpen, 2021)
Abstract Background The European Organisation for Research and Treatment of Cancer (EORTC) quality of life questionnaire for non-muscle invasive bladder cancer (QLQ-NMIBC24) has been available and applied for some years now, but has yet to undergo a full comprehensive psychometric evaluation. The aim of this study was to investigate the psychometric properties of the Dutch version of the EORTC QLQ-NMIBC24 questionnaire in patients with low, intermediate and high risk NMIBC. Methods We included patients newly diagnosed with NMIBC participating in the multicenter, population-based prospective cohort studies UroLife or BlaZIB. Psychometric evaluation included examination of the structural validity, reliability (i.e. internal consistency and test-retest reliability), construct validity (i.e. divergent validity and known-groups validity), responsiveness and interpretability. Results A total of 1463 patients who completed the baseline questionnaire of UroLife (n = 541, response rate 50%) or BlaZIB (n = 922, response rate 58%) were included. The percentage of missing responses were low for all non-sex related scales (< 1%) and ranged between 6.9% to 50.0% for sex-related scales. More than 15% of the patients obtained the lowest possible scores on nearly each scale (floor effect). The structural validity was adequate; the confirmatory factor analysis showed satisfactory results and all items of multiple items scales had higher within- than between-scale correlations. Reliability of the questionnaire was adequate for most multiple item scales (Cronbach's α ≥ 0.70 and intraclass correlation coefficient ≥ 0.70), with exception of the scales 'malaise' and 'bloating and flatulence'. The questionnaire also showed good construct validity; it showed low correlations with the items of the EORTC core questionnaire and was able to measure differences between risk-based subgroups. The responsiveness of the questionnaire was good, but the interpretability, i.e. minimal important change, could not be determined. Conclusions This study shows that the measurement properties of the EORTC QLQL-NMIBC24 are good; it has a good structural validity, reliability (i.e. internal consistency and test-retest reliability), construct validity (i.e. divergent validity and known-group validity), and responsiveness. Interpretability could not be assessed. This questionnaire can be used to measure and monitor health-related quality of life of patients with NMIBC.